Pengamatan morfologi β-tcp yang disintesis dari cangkang kerang hijau - Urrohman, Auliya; Eddy; Permata Setiana Putri, Tansza (Fakultas Kedokteran Gigi Universitas Trisakti, 2023)
β-Tricalcium Phosphate (β-TCP) is a biomaterial commonly used in dentistry as a bone substitute. β-TCP is a calcium phosphate compound where β-TCP requires a calcium source to be synthesized. The source of calcium could be obtained from green mussel shells because they have high calcium carbonate (CaCO3). The purpose of this study was to determine the effect of sintering temperature on the morphology of β-TCP synthesized from green mussel shells. The method of this research is an exploratory research conducted by knowing the effect of sintering temperature on the morphology of β-TCP synthesized from green mussel shells. The results of the synthesis were tested for characterized with a Scanning Electron Microscope (SEM). In the SEM characterization results, the higher the sintering temperature used in the sample, the more fused and resulting larger particle size. β-TCP with sintering temperature variations of 950℃, 1.000℃, 1.050℃ and 1.100℃ has a morphology consisting of small particles of irregular shape and bonding to each other to form micropores. The conclusion in this study is that the higher the sintering temperature applied, the more the particles coalesce and form larger particles.